Critical role for complement receptor C5aR2 in the pathogenesis of renal ischemia‐reperfusion injury. Issue 7 (10th April 2017) - Poppelaars, Felix; van Werkhoven, Maaike B.; Kotimaa, Juha; Veldhuis, Zwanida J.; Ausema, Albertina; Broeren, Stefan G. M.; Damman, Jeffrey; Hempel, Julia C.; Leuvenink, Henri G. D.; Daha, Mohamed R.; van Son, Willem J.; van Kooten, Cees; et al.
ABSTRACT: The complement system, and specifically C5a, is involved in renal ischemia‐reperfusion (IR) injury. The 2 receptors for complement anaphylatoxin C5a (C5aR1 and C5aR2) are expressed on leukocytes as well as on renal epithelium. Extensive evidence shows that C5aR1 inhibition protects kidneys from IR injury; however, the role of C5aR2 in IR injury is less clear as initial studies proposed the hypothesis that C5aR2 functions as a decoy receptor. By Using wild‐type, C5aR1 ‐/‐, and C5aR2 ‐/‐ mice in a model of renal IR injury, we found that a deficiency of either of these receptors protected mice from renal IR injury. Surprisingly, C5aR2 ‐/‐ mice were most protected and had lower creatinine levels and reduced acute tubular necrosis. Next, an in vivo migration study demonstrated that leukocyte chemotaxis was unaffected in C5aR2 ‐/‐ mice, whereas neutrophil activation was reduced by C5aR2 deficiency. To further investigate the contribution of renal cell‐expressed C5aR2 vs. leukocyte‐expressed C5aR2 to renal IR injury, bone marrow chimeras were created. Our data show that both renal cell‐expressed C5aR2 and leukocyte‐expressed C5aR2 mediate IR‐induced renal dysfunction. These studies reveal the importance of C5aR2 in renal IR injury. They further show that C5aR2 is a functional receptor, rather than a decoy receptor, and may provide a new target for intervention.—Poppelaars, F., van Werkhoven, M. B., Kotimaa, J., Veldhuis, Z. J., Ausema, A., Broeren, S. G. M., Damman, J., Hempel, J. C., Leuvenink, H. G. D., Daha, M. R., van Son, W. J., van Kooten, C., van Os, R. P., Hillebrands, J.‐L., Seelen, M. A. Critical role for complement receptor C5aR2 in the pathogenesis of renal ischemia‐reperfusion injury. FASEB J. 31, 3193–3204 (2017). www.fasebj.org